2017
DOI: 10.1177/0193945917729160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Web-Based Nursing Education’s Effects: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis investigated whether using web-based nursing educational programs increases a participant's knowledge and clinical performance. We performed a meta-analysis of studies published between January 2000 and July 2016 and identified through RISS, CINAHL, ProQuest Central, Embase, the Cochrane Library, and PubMed. Eleven studies were eligible for inclusion in this analysis. The results of the meta-analysis demonstrated significant differences not only for the overall effect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
2
26
0
2
Order By: Relevance
“…Nurse learning outcomes were reported in 18 of 22 SRs (82%) [1,3,4,10,36-38,40-47,49,51]. We divided learning into three subthemes: knowledge, attitude and self-efficacy, and skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurse learning outcomes were reported in 18 of 22 SRs (82%) [1,3,4,10,36-38,40-47,49,51]. We divided learning into three subthemes: knowledge, attitude and self-efficacy, and skills.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 SRs out of 22 (59%) [1,3,10,37,53,40-45,49,52], nurses improved their knowledge with the help of e-learning interventions on many topics, including assessment of ability of neurological function [42], medication administration and calculation [45], physiology and chronic health evaluation [10], arterial blood gas interpretation, intervention focusing on a rare disease [3], and palliative care [52]. With the help of e-learning, nurses improved their knowledge compared to no intervention [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as technology and a focus on efficiency becomes more profound in our society, in-services delivery methods have changed. In-services might now come in the form of pamphlets or via online platforms [ 22 ]. Yet, NAs in this study did not just want to be handed or provided information; they wanted to be shown and provided this information in the form of face-to-face contact.…”
Section: Discussionmentioning
confidence: 99%
“…In-services might now come in the form of pamphlets or via online platforms. 23 Yet, NAs in this study did not just want to be handed or provided information; they wanted to be shown and provided this information in the form of face-to-face contact. These ndings highlight the need to retain in-person trainings and ensure that NAs understand the information that they are receiving.…”
Section: Discussionmentioning
confidence: 99%